The Cultural Expression in the Local Television: The Cultural Political Economy Perspective - Puji Rianto; Hermin Indah Wahyuni; Sugeng Bayu Wahyono (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2025)
Since the beginning of the reformation era in 1998 and the enactment of Broadcasting Law No. 32/2002, local television channels has grown significantly. These emerging local television channels were expected to serve as an antithesis to Jakarta-based national television while also providing a space for cultural expression. This study investigates how local television express local culture using the cultural-political economy perspective. The research employs a case study with an instrumental case design and was conducted at ADiTV in Yogyakarta from April to September 2023. Data were collected through in-depth interviews, observations, and documentation. The findings indicate that local television stations like ADiTV play a crucial role in providing a platform for local cultural expression. However, as private broadcasting institutions, the cultural contents featured in programs such as Jenggleng Manasuka, Mocopat Syafaat, and Wedang Ronde cannot be separated from commercial motive. In other words, culture-based television programs are products of the cultural industry that must be marketable to generate profit, often making economic considerations more dominant. As a result, cultural expression on ADiTV becomes highly limited and fails to foster diverse cultural representations. This study concludes that economic interests shape the local cultural expression, as culture-based television programs are inherently part of the cultural industry—products intended for sale. This is a dimension often overlooked by researchers studying local television in Indonesia